Proteomic approaches to unravel complex interactions between Ganoderma boninense and oil palm in basal stem rot disease: a scoping review - Mohd Nayan, Noor Azlina; Sarizan, Nur Maisarah; Abd Hamid, Umi Marshida; Rusli, Mohd Hefni; Mohamed Mackeen, Muhammad Mukram; Abdullah, Mohd Faiz Foong (Faculty of Applied Sciences, 2025)
Ganoderma boninense poses the biggest threat to the oil palm industry by inducing basal stem rot (BSR) in Malaysia, a leading palm oilproducing nation. Protein analysis is one of the potential methods in early detection of infected plants by understanding the changes in protein molecules which are useful as biomarkers. However, proteomic methods are not widely used due to their complex protein analysis in nature and the diversity of protein characteristics, including variations in abundance, structure, and post-translational modifications. Thus, a scoping review was analysed based on related literatures by identifying gaps and limitations in protein analysis for managing G. boninense. This scoping review was conducted following PRISMA guidelines. The results were searched using different databases: Scopus, Asean Citation Index (ACI), ScienceDirect, PubMed, and Web of Science (WoS). The keywords used were "Ganoderma boninense" OR "basal stem rot" AND "proteomics" OR "protein analysis" OR "proteomic profiling" OR "mass spectrometry" OR "protein expression." 116 articles were collected from the various databases, and only 13 significant articles were included after reviewing the abstracts and removing the duplicates. The relevant articles showed that proteomic methods, particularly LC-MS, 2-DE, and MALDI TOF/TOF were effectively used to study the molecular reactions of oil palms to G. boninense infection. There was still a lack of proteomic data with other research on certain protein classes, and other post-translationally modified proteins which may contribute to an incomplete understanding of G. boninense pathogenicity. It is recommended that these gaps be addressed by employing advanced proteomic approaches in future studies to facilitate a deeper comprehension of complex protein interactions. The analysis of proteomic methods employed for studying G. boninense is essential for the oil palm sector, as this strategy can contribute to valuable insights that can advance strategies for early detection of the pathogen infection.